Mollusk shell δ¹⁸O in the past 1600 years in the Saloum Delta, Senegal - Carré, Matthieu; Azzoug, Moufok; Zaharias, Paul; Camara, Abdoulaye; Cheddadi, Rachid; Chevalier, Manuel; Fiorillo, Denis; Gaye, Amadou T; Janicot, Serge; Khodri, Myriam; Lazar, Alban; Lazareth, Claire E; et al. (Supplement to: Carré, M et al. (2019): Modern drought conditions in western Sahel unprecedented in the past 1600 years. Climate Dynamics, 52(3-4), 1949-1964, https://doi.org/10.1007/s00382-018-4311-3, 2018)
As climate model uncertainties remain very large for future rainfall in the Sahel, a multi-centennial perspective is required to assess the situation of current Sahel climate in the context of global warming. We present here the first record of hydroclimatic variability over the past 1600 years in Senegal, obtained from stable oxygen isotope analyses (δ18O) in archaeological shell middens from the Saloum Delta. During the preindustrial period, the region was relatively humid, with maximum humidity reached during the period from AD 1500 to AD 1800, referred to as the Little Ice Age. A significant negative link is observed at the centennial scale between global temperature and humidity in the Sahel that is at odds with the expected effects of latitudinal shifts of the intertropical convergence zone during the last millennium. In the context of the past 1600 years, the Western Sahel appears to be experiencing today unprecedented drought conditions. The rapid aridification that started ca. AD 1800 and the recent emergence of Sahel drought from the natural variability point to an anthropogenic forcing of Sahel drying trend. This new long-term perspective suggests that the recovery of Sahel rainfall in the last decade may only result from short-term internal variability, and supports climate models that predict an increase of Sahel drought under future greenhouse climate.